The trained leader and functional physiology: A theoretical study - Azzizi, Brahim; Hadjadj, Saad; Berkat, Hocine (Journal of Neonatal Surgery, 2026)
This article addresses an important topic in the field of psychological counseling and sports training, specifically functional physiology, exploring its foundations and hierarchy through its functional history. Physiology is one of the oldest sciences, a source of knowledge and ideas, particularly due to its relationship with other sciences, sports leadership, and the role of the coach. Physiology is connected to other sciences through exchange and overlap, including medicine, pharmacy, physiology, chemistry, biology, and others. Whether known by this name or another, the connection between physiology and medicine, or related sciences, is very close. It would be difficult to imagine any significant progress in one field that wasn't immediately reflected in the other. Their methods, despite their inherent differences, are closely related, and their common ground lies in the explanation of normal functions. These are medical practices aimed at responding to the urgent need to alleviate pain and provide treatment for illness..